Investigation of the Effect of Surface Crack on Low-Velocity Impact Response in Hybrid Laminated Composite Plates - Gunes, Aydin; Sahin, Omer Sinan (Springer Heidelberg, 2020)
Composite materials can be damaged in the environments in which they are used, due to the loads they are exposed to or due to different effects on the production processes. The formation processes of these damages generally develop as crack formation or progress of the existing crack. For this reason, it is very important to investigate the behavior of the crack that occurs after the dynamic loads to which the composite materials are exposed. In this study, the dynamic behaviors of hybrid laminated composites with different surface crack geometries were investigated. Surface cracks with different crack depth-to-thickness (a/t) and crack depth-to-crack width (a/c) ratios were machined upon hybrid composite laminates and subjected to low-velocity impact tests under 2 m/s, 2.5 m/s and 3 m/s impact velocities. The effect of different surface crack geometries upon variation of contact force versus time, variation of contact force versus displacement and variation of absorbed/rebound energy have been evaluated. The effect of surface crack geometry and impact velocity upon contact stiffness and bending stiffness was also evaluated. Damage formation during impact loading was examined by scanning electron microscopy and optical microscopy. After the evaluations, the damage behaviors caused by the dynamic loads depending on the initial surface crack geometry were examined in detail.
Keywords: Low-Velocity Impact; Hybrid Laminated Composite; Surface Crack; Dynamic Response; Delamination